WORD-OF-MOUTH MARKETING STRATEGIES BY SME PLAYERS IN THE DIGITAL ERA - Reza Juli Amri (GLOBAL RESEARCH IN ECONOMICS AND ADVANCE THEORY (GREAT), 2024)
This study examines the effectiveness of word-of-mouth (WOM) marketing strategies among small and medium-sized enterprises (SMEs) in the digital era, where customer trust in peer recommendations has grown significantly. Using a mixed-method approach (qualitative interviews with SME owners and quantitative surveys with customers) the research reveals that successful WOM strategies center on authentic customer engagement, social media utilization, and incentivized referral programs. The findings indicate that digital platforms significantly amplify WOM, allowing SMEs to extend their market reach while maintaining cost efficiency. However, challenges such as limited digital literacy and difficulties in managing negative feedback persist. Case studies demonstrate that storytelling, consistent interaction, and community building can enhance brand loyalty and organic growth. Statistical results from customer surveys show a strong correlation between positive WOM and increased customer trust, loyalty, and repeat purchases. This study concludes that authenticity and emotional resonance are crucial in maximizing WOM’s impact and recommends that SMEs invest in digital engagement skills, customer relationship management, and integrated marketing strategies to sustain WOM momentum. The research contributes to the academic discourse on SME digital marketing while offering actionable insights for practitioners seeking to grow their businesses through cost-effective, trust-based strategies.